The causal effects between low back pain and cerebrospinal fluid metabolites: a two-sample Mendelian randomization study - Run Peng; Xiaoxin Wang; Wei Wang; Zeqin Li; Yuze Sun; Mingliang Yang (Hereditas)
Abstract Background Observational studies have shown an association between cerebrospinal fluid (CSF) metabolites and low back pain (LBP), but the causal relationship between these factors remains unclear. Methods We performed a two-sample Mendelian randomization (MR) analysis to examine whether there is a causal relationship between CSF metabolites and LBP. We applied several MR methods, including inverse variance weighting, weighted median, MR-Egger, Wald ratio, and MR-PRESSO, to test the causal relationship and conducted a sensitivity analysis to assess the robustness of the results. Results We identified a total of 12 CSF metabolites significantly associated with LBP, of which Bilirubin, 5,6-dihydrothymine, Erythronate, Mannitol/sorbitol, and Butyrate have a potential inhibitory causal effect on LBP risk (p < 0.05). Meanwhile, 2-hydroxyadipate, Gamma-glutamyl-alpha-lysine, Indoleacetate, N-acetylputrescine, Palmitoyl dihydrosphingomyelin, S-methylcysteine, and 2,3-dihydroxy-5-methylthio-4-pentenoate play a causal role in increasing the risk of LBP (p < 0.05). No significant estimates of heterogeneity or pleiotropy were detected. Conclusion Our study emphasizes the causal relationship between CSF metabolites and LBP risk, providing reference for clinical treatment and prognosis of LBP.